The effect of Tn916 insertions on contour-clamped homogeneous electrophoresis patterns of Enterococcus faecalis. - Thal, L A (1997)
Contour-clamped homogeneous gel electrophoresis has increasingly been used and has generally been considered the method of choice for the delineation of enterococcial strains. It has been suggested that the contour-clamped homogeneous electric field (CHEF) electrophoresis digestion patterns of genomic DNA indicate the relatedness of strains when SmaI patterns differ by six or fewer bands. To evaluate the potential reasons for the diversity of bands among clonally related isolates, we studied plasmid-free Enterococcus faecalis FA2-2 and derivatives with transposon Tn916 (encoding for tetracycline resistance) insertions on the chromosome. We obtained derivatives with seven different Tn916 insertion sites and up to two copies of Tn916 on the chromosome, resulting in differences of one to seven bands by CHEF electrophoresis; eight different patterns were observed. With Tn916 insertions, there was either (i) loss of a band(s) with the generation of a new band(s), (ii) the generation of a new band(s) only, or (iii) the loss of a band(s) with no new visible band(s). These results indicate that strains can have up to seven different SmaI bands by CHEF electrophoresis and still be closely related.